Charles William Le Gendre papers - Le Gendre, Charles William, 1830-1899.
Correspondence, memoranda, dispatches, reports, Chinese and Japanese documents, and other papers relating chiefly to Le Gendre's diplomatic career in the American foreign service and in the Japanese and Korean governments. Documents his service as American consul at Amoy (Xiamen Shi), China (1866-1872); advisor in the Japanese foreign service and in a diplomatic post representing Japan in Taiwan (1872-1875); and advisor in the Korean government (1890-1899). Subjects include American interests in the Far East, Oriental civilizations, establishment of peaceful relations with Taiwan, and Korean trade relations. Includes Le Gendre's journal (4 volumes), with drawings and photographs, in which he recounts his travels among aborigines in Taiwan. Also includes a multivolume work by an unknown author, chiefly in French, pertaining to the development of various civilizations, the spread of races, and Asian history.
Army officer and diplomat.
Collection material in English and French, with Chinese and Japanese and other Asian languages.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Civilization, Oriental; Consuls -- China -- Xiamen Shi; Diplomatic and consular service, American -- China; Diplomatic and consular service, Japanese; Diplomatic and consular service, Japanese -- Taiwan; Ethnology; Taiwan aborigines; World history; Asia -- History; East Asia -- Foreign relations -- United States; Japan -- Foreign relations -- 1868-1912.; Japan -- Foreign relations -- Taiwan; Korea -- Commerce; Taiwan -- Description and travel; Taiwan -- Foreign relations; Taiwan -- Foreign relations -- Japan; United States -- Foreign relations -- 1865-1898.; United States -- Foreign relations -- East Asia; Army officers; Diplomats